In-line valve condition assessment by transient analysis - Zhihong Long; Gang Xu; Xiaoyan Chen; Yu Li; Tingchao Yu (Water-Energy Nexus)
Negligently partially closed in-line valves in pipes cause undesirable minor head losses that reduce the carrying capacity and increase operating costs attributable to energy consumption. However, few obtained results of in-line valves condition assessment has been offered in the literature. The paper makes further investigations on the interaction between the valve and the transient pressure wave, which provides experimental data support and reference opinions for the transient wave detection of in-line valve status with practical applications. The position of the in-line valve is evaluated by a simple equation and the propagation of transient pressure wave was analyzed. The relevant equations were derived and correlation analysis was performed. Based on the pressure-increase value, the head loss coefficient or valve opening degree could be determined, and feasible suggestions for detecting the valve opening degree using transient waves were made. Under the selected experimental conditions, the absolute error between the calculated valve opening degree and the actual opening degree was below 0.06 (1 for fully open valve opening and 0 for fully closed valve opening), proving that the valve opening assessment method was effective. This paper demonstrates the application of transient wave technology in real-time monitoring and assessment of valve positions. Through this technology, the valve positions in water distribution systems can be optimized effectively, thereby reducing resistance losses, meeting varying water demands, avoiding unnecessary energy waste, and enhancing the overall energy efficiency of the water supply system.